The economics of technology and employment : theory and empirical evidence - Vivarelli, Marco, 1963- (E. Elgar Pub., 1995)
The impact of technical change on employment is investigated in this important new book which offers a critical appraisal of how far current economic analysis and theory can deal with this key policy issue. The Economics of Technology and Employment addresses the impact of technical change on employment from both theoretical and empirical perspectives. After an analytical discussion of theoretical propositions and models put forward by classical and contemporary economists, Dr Vivarelli develops a model to examine the extent to which worker displacement due to technical progress can be offset by compensatory market forces. This model is tested using Italian and US aggregate time-series data. The theoretical discussion and empirical results are combined to demonstrate that the employment impact of labour-saving technologies can only be partially counter-balanced by market forces and so economic policy measures could be necessary.